Docência em língua inglesa nas perspectivas crítica e sócio-histórico-cultural: as experiências de dois alunos-professores em formação inicial na disciplina de estágio supervisionado - Pereira, Paula Graciano (2013)
This study focuses on pre-service English teachers’ education under critical and socialhistorical- cultural perspectives throughout the course of supervised practicum. The main goal of this research is to understand the meanings the participants build about teaching English as a carrier. It also aims at identifying and analyzing the senses attributed by the participants to the English language and its teaching-learning, as well as identifying and analyzing the participants’ perceptions of teaching English as a carrier. This research was held during the first semester of 2010, at Universidade Federal do Tocantins, and had the participation of two student-teachers at their last term at Letras Portuguese- English course. A qualitative approach was adopted to collect and to analyze the data in this case study. The data were obtained by means of a questionnaires, interviews, observation, field notes, audio and video recording and written tasks done by the participants. The data were then analyzed under the conceptions of socio-historicalcultural theory and Critical Applied Linguistics. Amongst the conclusions found, we observed that the participants present varied and many times contradictory conceptions, postures and attitudes towards their perceptions of the English language, its teachinglearning and what it means to be an English teacher nowadays. For the studentsteachers, the English language can assume different meanings, with emphasis on those regarding its relations with the market, globalization and cultural imperialism. The role English can assume as a social inclusion or exclusion factor was also highlighted by the participants. Another conclusion we arrived at concerns the meanings attributed to teaching English as a carrier and the choice for this profession, which is perceived by the participants as a complex and tiresome carrier, with low social and financial acknowledgement. However, on the other hand, it was also pinpointed that it is a very important profession for the construction of a fairer and more equalitarian society.